The tree in me - Luyken, Corinna (2021)
Through text and illustrations of children reveling in nature, explores the various ways we as human beings are strong, creative, and connected to others
Ages 4-8.
Grades K-1.
Keywords: Nature stories; Self-esteem -- Juvenile fiction; Conduct of life -- Juvenile fiction; Trees -- Juvenile fiction